The Contribution of E-Commerce to Economic Growth in The Covid-19 Era - Heliyani heliyani; Evi Susanti Tasri; Dona Amelia; Yudi Dwianda (Economics Development Analysis Journal, 2023)
The e-commerce business sector is a sector that has undergone considerable changes due to the COVID-19 pandemic. This study aims to examine the impact of the decline in e-commerce revenue due to the COVID-19 pandemic on Indonesia's economic growth. The decline in e-commerce revenue was influenced by the number of e-commerce itself and the information technology training received by e-commerce business actors as well as the number of Small and Medium Enterprises (SMEs) in Indonesia. The analytical method used in this research is Partial Least Square Structural Equation Modeling (PLS-SEM). This study found that the number of SMEs, information technology and e-commerce training had a negative effect on the decline in e-commerce revenues in the era of the covid-19 pandemic. This study also found that the decline in e-commerce revenue in the era of the Covid-19 pandemic in Indonesia had an impact on Indonesia's economic growth. This study also shows the results that a significant decrease in e-commerce income partially mediates the variables of the e-commerce and SME sector on economic growth. However, information technology training can be fully mediated on economic growth